2011
DOI: 10.1159/000333400
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyoma of the Ileum Leading to Intussusception

Abstract: Adenomyoma of the ileum is a rare condition. A 68-year-old Japanese man presented with nausea and distension of the abdomen. Enhanced computed tomography of his abdomen revealed wall thickening in the ileum and dilation of the proximal small intestine. Open laparotomy was performed to find the cause of the patient’s small bowel obstruction, and a tumor was found in the ileum, which had resulted in intussusception. The tumor and 20 cm of the adjacent ileum were resected. The resected specimen displayed a macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Clinically, our case presented with intussusceptions caused by adenomyomas of the ileum. To our knowledge, our case is the first report of two synchronous adenomyomas of small intestine, and the third report of adenomyomas causing intestinal intussusceptions in an adult .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Clinically, our case presented with intussusceptions caused by adenomyomas of the ileum. To our knowledge, our case is the first report of two synchronous adenomyomas of small intestine, and the third report of adenomyomas causing intestinal intussusceptions in an adult .…”
Section: Discussionmentioning
confidence: 62%
“…Table 1. Review of the literature: Clinicopathological findings of adenomyoma of the small intestine [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Below, we summarize the characteristics of the 20 previous cases of adenomyoma of the ileum reported in English language literature (table 1) [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Abdominal CT…”
Section: Discussion:-mentioning
confidence: 99%
“…5 While the incidence of small intestine adenomyoma is relatively rare, the actual incidence is unclear because very few cases have been reported. Review of the literature reveals 34 reported cases in the small intestine, 3,[5][6][7][8][9][10][11][12][13][15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34] including the duodenum, ampulla of Vater, and ileum, with 11 well-documented cases reported in the jejunum (Table 1). 3,5,9-10,16-17, 20-21,29,31,34 Of these cases, the patients were between the ages of three to eighty one years old, with six women and five men.…”
Section: Discussionmentioning
confidence: 99%
“…In the small intestine, intussusception is its most common complication, reported in 19 cases. [1][2][3][6][7][8][11][12][13][15][16][17][18][19][20][24][25]27,[32][33] Anemia has been reported in 11.7% of the cases described (4 cases). A-B, 200x).…”
Section: Discussionmentioning
confidence: 99%